From tech to touch: Self-concept and testimonials in AR try-on versus website - Aleem, A.; Loureiro, S. M. C.; Martinho, J. (Journal of Research in Interactive Marketing, 2023)
Purpose One of the main challenges that brands face is the ability to provide a real-life experience through online platforms. The aim of this study is to analyze consumers' self-concept and testimonials through an augmented reality (AR) try-on app versus a website. Design/methodology/approach An online survey was conducted with 222 participants, in which they were randomly exposed to two scenarios: AR try-on app or website experience and positive versus negative reviews presence. Findings The findings indicate positive effects of ideal self-congruence on purchase intention and confidence in fit. Low self-esteem consumers experience greater ideal self-congruence using AR when compared to the website. Confidence in fit partially mediates between ideal self-congruence and purchase intention. Higher levels of diagnosticity of reviews conduct to higher levels of purchase intention. Originality/value This study contributes to interactive marketing by exploring the effect of appearance self-esteem in the relationship between AR app versus website and ideal self-congruence and how this influences consumer behavior. In addition, the study also emphasizes the role of testimonials in shaping consumer intentions.